The effects of pregnancy on oral health, salivary ph and flow rate - Fatma Yilmaz; Ozgul Carti Dorterler; Saniye Eren Halici; Burcu Kasap; Aysegul Demirbas (BMC, 2024)
Abstract Background The frequent occurrence of dental caries and periodontal diseases in women during pregnancy may be due to many factors, such as salivary variables. The aim of this study was to evaluate the effects of pregnancy on salivary pH, flow rate, the DMFT index, and CPI sores. Methods A total of 198 volunteers (pregnant in different trimesters and non- pregnant) were included for the present observational cross-sectional study. Data about sociodemographic characteristics and dental and systemic health conditions were recorded. Unstimulated saliva samples were collected for 5 min via the spitting method. The pH of the saliva was measured by a portable pH meter. The salivary flow rate was determined by the weight measurement method. The DMFT index and CPI were determined. The statistical evaluation was performed using Robust ve Poisson Regression analyses (p < 0.05). Results It was determined that there was a gradually significant decrease in the Ph value from the first trimester to the third trimester during pregnancy, which was lower than the control group. (p < 0.001) The flow rate of pregnants in their third trimester was lower than that of first trimester (p = 0.017). The CPI scores of pregnant women were significantly greater than that of non-pregnants (p = 0.042), while the DMFTs were similar among all groups. Conclusion Our findings indicate that pregnancy leads to a notable reduction in unstimulated salivary pH and flow rate, which also has a detrimental impact on periodontal health. Trial registration Clinical Trials-ID: NCT06343337; Registration Date: 04.01.2024.